Fine-tuned nitric oxide and hormone interface in plant root development and regeneration - Sanchez-Corrionero, Alvaro (Journal of experimental botany, 2023)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology.